Intrinsic Nonlinear Hall Effect in Antiferromagnetic Tetragonal CuMnAs - Wang, Chong; Gao, Yang; Xiao, Di (Physical review letters, 2021)
Detecting the orientation of the Néel vector is a major research topic in antiferromagnetic spintronics. Here we recognize the intrinsic nonlinear Hall effect, which is independent of the relaxation time, as a prominent contribution to the time-reversal-odd second order conductivity and can be used to detect the reversal of the Néel vector. In contrast, the Berry-curvature-dipole-induced nonlinear Hall effect depends linearly on relaxation time and is time-reversal even. We study the intrinsic nonlinear Hall effect in an antiferromagnetic metal: tetragonal CuMnAs, and show that its nonlinear Hall conductivity can reach the order of mA/V^{2}. The dependence on the chemical potential of such nonlinear Hall conductivity can be qualitatively explained by a tilted massive Dirac model. Moreover, we demonstrate its strong temperature dependence and briefly discuss its competition with the second order Drude conductivity. Finally, a complete survey of magnetic point groups is presented, providing guidelines for finding more antiferromagnetic materials with the intrinsic nonlinear Hall effect.